Comparison of absolute neutrophil count between premature and term infants - Ahmad Faisal; Guslihan D Tjipta; Bidasari Lubis; Dachrul Aldy (Indonesian Pediatric Society Publishing House, 2016)
Background Neutrophils are very important in the body defense against bacterial infection. Absolute neutrophil count (ANC) could be used for the recognition of early-onset bacterial sepsis in neonates. Objective The aim of this study was to compare the value of ANC between premature and term infants, to assess the prevalence of early-onset neutropenia in premature infants and its relationship with prematurity, and to find out the correlation between gesta- tional age and ANC. Methods A cross-sectional study was conducted during February to May 2003. Subjects were newborn infants with gestational age of less than 37 weeks who were born in Adam Malik and Pirngadi Hospitals, Medan. Newborn infants with severe asphyxia (5-minute Apgar score of less than 4), fever, seizure, and maternal hypertension were excluded. Complete blood count was done by means of automatic cell counter (Micros (R) , Germany). Term healthy infants were used as control subjects. Results ANC differed significantly between both groups (p=0.0001). The prevalence of early-onset neutropenia in premature infants was 9% (95%CI 0.065;0.21). Prematurity was related with the incidence of neutropenia with a prevalence ratio of 1.1. There was a weak positive correlation between gestational age and ANC with an r-value of 0.49 (p=0.0001). Conclusions ANC in premature infants differs from that in term infants. The prevalence of early-onset neutropenia in premature infants was 9% (95%CI 0.065;0.21). Prematurity is related with the incidence of early-onset neutropenia in newborn infants. There is a correlation between gestational age and ANC